Polistes (Polistella) wasps (Hymenoptera: Vespidae: Polistinae) from mountainous areas of northern Vietnam, with description of five new species - Nguyen, Lien Thi Phuong; Kojima, Jun-Ichi; Saito, Fuki (Zootaxa, 2011)
A total of 14 species of subgenus Polistella Ashmead 1904 of genus Polistes Latreille 1802 are recognized in the mountainous areas of northern Vietnam, the eastern margin of the eastern slope of the Himalayas. A key to these species is provided. Five new species are described: P. curcipunctum Nguyen, Kojima & Saito, sp. nov.; P. reliciniclypeus Nguyen, Kojima & Saito, sp. nov.; P. gilvus Nguyen, Kojima & Saito, sp. nov.; P. paco Nguyen, Kojima & Saito, sp. nov.; and P. clandestinus Nguyen, Kojima & Saito, sp. nov. The male of P. dawnae Dover & Rao is described for the first time. Nests of P. lepcha Cameron, P. dawnae Dover & Rao , P. reliciniclypeus and P.